On the efficiency properties of the Roy's model under asymmetric information - Concetta Mendolicchio; Tito Pietra (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
We consider Roy's economies with perfectly competitive labor markets and asymmetric information. Firms choose their investments in physical capital before observing the characteristics of the labor markets they will face. We provide conditions under which equilibrium allocations are constrained Pareto efficient, i.e., such that it is impossible to improve upon the equilibrium allocation by changing agents' investments and letting the other endogenous variables adjust to restore market clearing. We also provide a robust example of a class of economies where these conditions fail and where equilibria are characterized by overinvestments in high skills. Finally, we discuss some implications of our main results for the optimal taxation literature. – – Wir untersuchen Roy'sche Modellökonomien mit perfekt kompetitiven Arbeitsmärkten und asymetrischen Informationen. Firmen entscheiden über ihre Investitionen in Sachkapital bevor ihnen die Charakteristiken des Arbeitsmarktes bekannt sind. Wir bestimmen Bedingungen unter denen die Gleichgewichtsaufteilung beschränkt Pareto effizient ist, d.h. es ist unmöglich die Gleichgewichtsaufteilung durch Änderungen im Investitionsverhalten zu verbessern und die anderen endogenen Variablen sich so anpassen zu lassen, dass die Markträumung wieder hergestellt wird. Wir zeigen anhand eines robusten Beispiels mit einer Klasse an Modellökonomien bei denen diese Bedingungen verletzt sind und bei denen die Gleichgewichte durch Überinvestitionen in hohe Qualifikationen gekennzeichnet sind. Schließlich diskutieren wir einige Implikationen unserer Hauptresultate für die Forschung zur optimalen Besteuerung.
Keywords: D60; D82; J24; 330; Roy's model; human capital; constrained Pareto efficiency